Psychosomatic Symptoms in Terminally Ill Cancer Patients and Its Relation With Using Complementary and Alternative Medicines: A Cross-Sectional Study in Southeast Iran - Dehghan, Mahlagha; Hoseini, Fatemeh Sadat; Zakeri, Mohammad Ali (Frontiers in Psychiatry, 2022)
Background: Cancer patients face various problems and complications, which they address through various complementary and alternative medicines (CAM). The aim of this study was to investigate the relationship between CAM and psychosomatic symptoms in terminally ill cancer patients. Methods: This cross-sectional study was performed on 221 terminally ill cancer patients in southeastern Iran. Convenience sampling was used to select patients who met the inclusion criteria and referred to oncology centres and doctors' offices. Using questionnaires like Demographic information questionnaire, Edmonton Symptom Assessment Scale, Hospital Anxiety and Depression Scale, CAM questionnaire and satisfaction with the use of CAM, the researcher was able to compile a comprehensive picture of the population. Results: Last year, 87.3 percent of the participants used at least one type of CAM. Aside from prayer, 42.1 percent of the participants used at least one type of CAM in the last year. Furthermore, 48.4 percent of the participants used only one type of CAM, 29.9 percent used two types of CAM, 5.4 percent used three types of CAM, and 3.6 percent used four to five types of CAM last year. Prayer was used by 83.7 percent of the participants, medicinal plants by 35.8 percent, massage by 9.5 percent, dietary supplements by 3.6 percent, wet cupping by 3.2 percent, relaxation and meditation by 2.7 percent, dry cupping by 2.4 percent, and acupuncture by 0.5 percent. The common reason for using CAM was to reduce the stress and anxiety caused by cancer and to treat it. 62.5 percent sought advice from a doctor before using dietary supplements, 42.9 percent sought advice before using wet cupping, and 20 percent sought advice before using dry cupping. Conclusion: Patients with cancer have an elevated level of anxiety, and the primary reason for using CAM was to relieve stress and anxiety associated with cancer and to treat it. However, physical and psychological symptoms are the same for CAM and non-CAM users. Due to the widespread use of CAM by cancer patients, future studies should examine the reasons for and effects of CAM use.